Potential of Multidimensional, Large-scale Biodatabases to Elucidate Coagulation and Platelet Pathways as an Approach towards Precision Medicine in Thrombotic Disease - Panova-Noeva, Marina; Eggebrecht, Lisa; Prochaska, Jürgen H.; Wild, Philipp S. (Hämostaseologie, 2019)
Cardiovascular and especially thrombotic diseases remain a major cause of morbidity and mortality worldwide. In past years, significant improvements in understanding disease processes, risk assessment, and prediction of clinical outcome in the field of thrombosis and haemostasis have been made by using large-scale biodatabases. These important research resources enable a comprehensive research approach by integrating clinical, environmental, genomic, and molecular information. Cutting edge, high throughput technologies open new data dimensions for clinical large-scale investigations. Joining multiple information levels from several pathophysiological pathways in contrast to a single marker approach might better model the complexity of disease pathogenesis. This review focuses on the possibilities that ultimately allow conducting wide-scale analyses for unravelling the multifaceted interplay between coagulation and cellular (e.g., platelets) elements in the development of thrombotic disease. It further provides examples for the use of biodatabases in the field of venous thromboembolism, explores the links between venous and arterial thrombotic diseases, and finally informs on the current use of platelet biomarkers in the thrombosis and haemostasis field.
Keywords: epidemiology; biodatabase; coagulation; platelets